Gallocatechin from Uncaria gambir Roxb as a MurB Inhibitor: A Molecular Docking Analysis and Its Therapeutic Implications: Research Article - Ilham Kurniawan (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
The rapid escalation of antimicrobial resistance demands new antibacterial strategies targeting essential and druggable bacterial enzymes. Here, we report the molecular characterization of gallocatechin, a polyphenolic compound from Uncaria gambir, as a potential inhibitor of MurB from Pseudomonas aeruginosa (PDB ID: 7ORZ), a key enzyme in peptidoglycan biosynthesis. Docking protocol validation via redocking of the co-crystallized ligand yielded high structural accuracy (RMSD = 0.991 Å). Gallocatechin exhibited a markedly enhanced binding affinity (−8.1 kcal/mol) relative to the reference ligand (−5.3 kcal/mol), corresponding to an approximately 100-fold lower predicted inhibition constant (Ki ≈ 1.09 µM vs 131 µM). Structural analysis revealed that gallocatechin establishes a dense and multi-modal interaction network, simultaneously engaging the catalytic triad (Arg166, Ser239, Glu335) through hydrogen bonding and complementary electrostatic interactions. Notably, this tri-residue engagement and dual electrostatic stabilization are rarely observed in previously reported MurB inhibitors. The binding mode supports a dual inhibitory mechanism involving both competitive substrate displacement and perturbation of the NADPH-dependent catalytic cycle. Collectively, these findings position gallocatechin as a structurally distinct and mechanistically promising scaffold for MurB inhibition, providing a rational basis for the development of next-generation antibacterial agents targeting multidrug-resistant P. aeruginosa. Further experimental validation is warranted to confirm its therapeutic potential.